Categorising implementation determinants and strategies within the US HIV implementation literature: a systematic review protocol - Justin D Smith; Brian Mustanski; Virginia McKay; James Lorenz Merle; Dennis Li; Brennan Keiser; Alithia Zamantakis; Artur Queiroz; Carlos G Gallo; Juan A Villamar; Juan Pablo Zapata; Nanette Benbow (BMJ Open, 2023)
Introduction Despite decreased rates of new infections, HIV/AIDS continues to impact certain US populations. In order to achieve the goals laid out in the Ending the HIV Epidemic (EHE) in the US initiative, implementation science is needed to expand the sustained use of effective prevention and treatment interventions, particularly among priority populations at risk for and living with HIV/AIDS. Over 200 HIV-related implementation studies have been funded by the US National Institutes of Health. Therefore, a comprehensive review of the literature identifying implementation determinants (barriers and facilitators) and categorising implementation strategies across the continuum of HIV prevention and care in the USA is appropriate and needed to enhance current knowledge and help achieve the goals laid out in the EHE national strategic plan.Methods and analysis This systematic review protocol follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Between November 2020 and January 2022, a broad database search strategy of Ovid MEDLINE, PsycINFO and Web of Science was conducted to capture implementation-related studies along the HIV prevention and care continuum. Articles were eligible for inclusion if they were: conducted in the USA, published after the year 2000, written in English, related to HIV/AIDS, focused on outcomes related to dissemination and implementation (ie, did not test/evaluate/explore implementation determinants or strategies) and were behavioural studies (ie, not basic science). We plan to conduct three systematic reviews to identify and categorise determinants and strategies associated with three HIV focus areas: pre-exposure prophylaxis, testing/diagnosing and linkage to care, and treatment. Determinants will be coded according to an adapted Consolidated Framework for Implementation Research 2.0. Implementation strategies and outcomes will be categorised in accordance with existing taxonomies and frameworks.Ethics and dissemination Ethics approval is not applicable. No original data will be collected. Results will be disseminated through peer-reviewed publications, conference presentations and via online tools.PROSPERO registration number CRD42021233089.